Chapter 1 Introductio; Controlled Document Authoring in a Machine Translation Age (2020)
In this digital age, we have witnessed an increasing proliferation of information that is digitally created and disseminated online. In conjunction with this, rapid advances in translation technologies, such as machine translation (MT), have promoted the multilingualisation of digital text. Not only companies but also governments have increasingly adopted commercially or freely available MT systems to create translations in multiple languages to reach a wide audience. End users themselves can take advantage of online MT services to obtain information communicated in languages that they cannot understand. In the context of Japanese municipalities, which is the main focus of this book, a variety of information is published online regarding not only regional events and tourism, but also certain procedures that must be complied with when living in the municipalities (e.g. registering residency with the local city hall; sorting and recycling garbage; taking action in the case of emergencies). In general, such texts are produced in the official language(s) of the country—in our case, Japanese. There are, however, many foreign residents who do not have the Japanese language skills necessary to understand official documents written in Japanese. Although some of the larger municipalities provide human translations of their websites into various other languages spoken by local communities, the target languages are limited, usually to English alone. Moreover, the scope of the translated versions is often much more restricted than the original Japanese documents since, as ?, p.386 points out, ‘to expect local governments with limited resources to translate their entire websites into one or more foreign languages would be unrealistic’. In most small municipalities, resources are so scarce that they cannot even provide English translations. Under such circumstances, municipalities typically rely on MT tools, or else the residents themselves rely on MT, such as Google Translate, to grasp the meaning of texts.